Reversible and Irreversible Alterations of Human Plasminogen Indicated by Changes in Susceptibility to Plasminogen Activators and in Response to ∈-Aminocaproic Acid - Thorsen, Sixtus; Kok, Preben; Astrup, Tage (Thrombosis and Haemostasis, 1974)
Increasing concentrations of EACA produce a biphasic pattern of inhibition and enhancement of urokinase-induced lysis of bovine fibrin containing bovine plasminogen, while the inhibition of fibrinolysis induced by a porcine tissue plasminogen activator increases uniformly. The biphasic EACA pattern is also observed with human plasminogen in fibrinolytic and caseinolytic assays of urokinase. The biphasic EACA pattern produced with urokinase is related to the presence of a genuine form of plasminogen. The enhancement phase is caused by an increased rate of plasminogen activation in the presence of EACA. A brief treatment of genuine plasminogen with acid at ionic strength 0.15 results in an enhanced susceptibility to plasminogen activators and in a partial abolishment of the biphasic response. These acid-induced alterations of plasminogen seem to be reversed by acid dialysis at low ionic strength. Other preparations of plasminogen with enhanced susceptibility to activators have lost the ability to produce a biphasic pattern of inhibition and enhancement of urokinase-induced plasminogen activation in the presence of EACA and this ability does not return after acid dialysis at low ionic strength. EACA inhibits all plasmin preparations, whether prepared from genuine or altered forms of plasminogen, in the same uniform manner.Our results show that different forms of plasminogen can be identified by differences in the susceptibilities to activators, by their response to EACA, and by the reversibility or irreversibility of the alterations.